2013
DOI: 10.1007/s00701-013-1634-z
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid haemorrhage WFNS grade V: is maximal treatment worthwhile?

Abstract: Despite treatment, initial mortality and severe disability remain high. Nevertheless, a favourable outcome was achieved in 26 % of aggressively treated patients, rendering the withdrawal of maximal therapy for WFNS grade V SAH patients unacceptable today. In cases of old patients with IVH, the indication for aggressive therapy should be put in place more carefully due to a very poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 24 publications
4
65
1
Order By: Relevance
“…The association between poor‐grade SAH with worse outcomes has frequently led to the conventional delaying or denial of maximal therapy for this group of patients, where, if no surgical treatment is offered, the risk of mortality can be as high as 75–100 per cent . However, the advent of improved neurocritical care and endovascular therapy has precipitated appeals for the aggressive treatment of poor‐grade SAH patients . In a review of 138 patients with grade V SAH, where more than one‐third (37 per cent) had at least one fixed dilated pupil, 26 per cent of patients had a favourable outcome without significant neurological deficits or with slight disability (mRS ≤2) at a median follow‐up period of 20 months .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between poor‐grade SAH with worse outcomes has frequently led to the conventional delaying or denial of maximal therapy for this group of patients, where, if no surgical treatment is offered, the risk of mortality can be as high as 75–100 per cent . However, the advent of improved neurocritical care and endovascular therapy has precipitated appeals for the aggressive treatment of poor‐grade SAH patients . In a review of 138 patients with grade V SAH, where more than one‐third (37 per cent) had at least one fixed dilated pupil, 26 per cent of patients had a favourable outcome without significant neurological deficits or with slight disability (mRS ≤2) at a median follow‐up period of 20 months .…”
Section: Discussionmentioning
confidence: 99%
“…However, the advent of improved neurocritical care and endovascular therapy has precipitated appeals for the aggressive treatment of poor‐grade SAH patients . In a review of 138 patients with grade V SAH, where more than one‐third (37 per cent) had at least one fixed dilated pupil, 26 per cent of patients had a favourable outcome without significant neurological deficits or with slight disability (mRS ≤2) at a median follow‐up period of 20 months . In particular, initial pupillary status was not a predictor of outcome .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zentner et al [41] reported that early surgery resulted in a good outcome of 22% of patients with the worst grade. A study of 103 patients with grade V showed a good outcome in 26% of patients at follow-up [42]. Despite the rates of morbidity and death remaining high in patients with WFNS grade V, these findings suggest that early aneurysm repair is feasible and safe for poor-grade aSAH.…”
Section: Timing Of Treatmentmentioning
confidence: 99%
“…Ultra-early treatment (within 24 h) reduces the risk of rebleeding and improves outcomes in most patients with good-grade aSAH [46][47][48]. However, there is no evidence to support ultra-early treatment of poorgrade aSAH because these patients experience more severe brain swelling than good-grade patients [42,49]. With development in microsurgical techniques, there has been growing interest in ultra-early treatment of aSAH.…”
Section: Timing Of Treatmentmentioning
confidence: 99%